Pengaruh Tumpang Sari Cabai dengan Kubis terhadap Hama dan Penyakit Tanaman Cabai Di Desa Kerinjing Kota Pagar Alam - Arsi Arsi; Gunawan Ade Putra Sihite; Fitra Gustiar; Irmawati Irmawati; Suparman SHK; Harman Hamidson; Chandra Irsan; Suwandi Suwandi; Yulia Pujiastuti; Khodijah Khodijah; Nurhayati Nurhayati; Abu Umayah; Bambang Gunawan; Andika Tiara Sukma; Kevin Christian Bakkit P (Seminar Nasional Lahan Suboptimal, 2021)
Arsi A, Sihite GAP, Gustiar F, Irmawati I, SHK Suparman, Hamidson H, Irsan C, Suwandi S, Pujiastuti Y, Khodijah K, Nurhayati N, Umayah A, Gunawan B, Sukma AT, Bakkit PKC.  2021. The effect of intercropping chili with cabbage on pests and plant disease in Kerinjing Village Pagar Alam city. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang 20 Oktober 2021. pp.101-113. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Red chili (Capsicum annuum) belongs to the family Solanaceae and is one of the vegetable commodities that has many benefits, high economic value. The aim of this field practice is to find out the difference in intensity of pest and disease attacks on intercropping and monoculture chili plants. This field practice was carried out in Kerinjing Village, Dempo Utara District, Kota Pagar Alam, South Sumatra. The reseach uses the case method by deliberate sampling in a field by counting the number of mounds in the field and determining the sample on the mound to be observed. On the two fields that were observed were found pests and diseases that attacked the chili plants namely mandibular pests and curly diseases, yellow disease and leaf spot disease. The average intensity of mandibular pest attacks on monocultures is 2.7% while on intercropping is 11.12%. The mean intensity of attacks of curly diseases was 33.87% in monocultures and 22.35 in intercropping. In jaundice, the mean intensity of attack was 14.87% in monoculture land and 8.25% in intercropping land while the mean intensity of spotting was 5.67% in monoculture land and 1.30% in intercropping land. From the observations that have been made that there is no significant difference between monoculture land and intercropping land for pests and diseases of chili plants. Weather affects the attack of pests and diseases on both fields, where dry weather affects the spread of disease-causing vectors so that the intensity of the attacks is higher. And also the use of crop rotation that is not right also exacerbates the level of pest and disease attacks on chili plants.